FINANCIAL DETERMINANTS OF EDUCATIONAL RESOURCES MANAGEMENT FOR ENHANCING STUDENTS’ PERFORMANCE IN SECONDARY SCHOOLS IN VIHIGA COUNTY, KENYA - Ayoti, Caroline; Koteng, Dr. Grace; Odhiambo, Dr. Raphael Ongunya (IJRDO - Journal of Applied Management Science, 2016)
Resource utilization is an integral part of the overall management of the school. Education in a school is explored by provision of resources, their maximum utilization and management. Proper management of resources enhances students’ performance and achieves the educational objectives. The success or failure of any organization, business or enterprise depends highly on proper management of human and material resources. The purpose of this study was to establish the financial determinants of management of educational resources for enhancing students’ performance in secondary schools in Vihiga County. A descriptive survey design was adopted. The study population composed of 112 head teachers, 1,120 teachers, 4,480 students and 9 County Quality Assurance and Standards Officers. Simple random sampling method, stratified sampling technique, saturated sampling technique and purposive sampling method were used to select samples. Questionnaires and in-depth interview guides, observation schedules and document analysis were used to collect data. Reliability of instruments was determined through a pilot study conducted in 3 secondary schools. Results of reliability of the instruments were assessed using Pearson’s product moment correlation coefficient test. Content validity was established by availing instruments to supervisors. Qualitative data from interviews was transcribed and reported according to emerging themes, categories and sub-categories while quantitative data was analyzed using descriptive statistics such as frequency counts, means and percentages. Pearson’s product moment correlation coefficient was used to establish relationships between variables. Findings of the study revealed that the inadequacy of financial resources in schools in Vihiga County had a negative impact on acquisition of relevant and adequate educational resources and this also impacted negatively on performance of students in KCSE exams. From the study it is concluded that procurement of resources mainly depend on fee collection, proceeds from income generating activities, fund raising activities (Harambee), bursaries,